Future of AI & Generation Alpha: ChatGPT beyond Boundaries - Dr. Bharati Rathore (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2023)
Open AI has the potential to drastically improve many aspects of our lives, including through the use of chatbots. Chatbots are able to automate many tasks and processes, thus streamlining communication, increasing efficiency, and providing a more user-friendly experience. OpenAI's Chat Generative Pre-trained Transformer (ChatGPT) has revolutionized the way artificial intelligence can interact and communicate with humans.ChatGPT enables natural language processing and automated text generation, and has the potential to significantly improve the way we interact, communicate and engage with machines. The development of AI tools such as ChatGPT is poised to have a major impact on how scientific articles are written and reviewed, as AI continues to rapidly advance.AI tools have the potential to streamline the academic writing process by automating tasks, intelligently analyzing data and providing better recommendations, resulting in more efficient, time saving and accurate writingby providing automation, intelligent analysis and better recommendations. This research aims to explore user expectations AI, and gain insight into their use and impact in near future. In order to alter and understand the content of these AI tools, we also used ChatGPT and other previous studies to collect qualitative data. This research also focuses on predictive “MESN Model” for forecasting through ChatGPT.